Nutritional Antioxidants Mechanisms of Action, Analyses of Activities and Medical Applications - Vaya, J.; Aviram, M. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2001)
The important role of dietary antioxidants in maintaining the integrity of living organisms is gaining ever-increasing recognition.New data are constantly gathered to show the role of oxidative stress and the involvement of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in the pathogenesis of degenerative diseases. These diseases are associated with a disturbance in the necessary balance between oxidation and reduction status in blood and tissues, leading to oxidation of lipids, proteins and nucleic acids. Such oxidative damage is accompanied by changes in macromolcules structure and function and by the manifestation of clinical disorders such as cardiovascular diseases and cancer. Hence, widespread research is being conducted aiming to investigate the possible effects and mechanisms of action of dietary antioxidants in these diseases.The present review focuses on the types of the various natural antioxidants, their tissue distribution, bio-availability, mechanisms of actions and therapeutical applications. Antioxidants may exert their effect on biological systems by different mechanisms including electron donation (as reducing agents), metal ion chelation (thereby eliminating potential free radicals), sparing of antioxidants (co-antioxidants) or by genes expression regulation. The various methods currently in use for determination of antioxidant activities and the role of antioxidants in the management of human diseases are discussed.
Keywords: Quantum chemical calculation